A Systematic Review of the Effects of Paternity Leave on the Health and Well-Being of Mothers and Children - Maharani, Fadiah; Herbawani, Lindya Okti; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi; Adepoju, Victor Abiola (Public Health of Indonesia, 2025)
Background: The role of fathers in childcare is increasingly recognized as essential to promoting family well-being, particularly through the provision of paternity leave policies that enable fathers to participate actively in caregiving during the early stages of a child's life. Empirical evidence suggests that paternal involvement has significant positive impacts on maternal health and child development. However, the implementation and effectiveness of paternity leave policies remain inconsistent across countries, with many failing to utilize them optimally to support familial health. Objective: This systematic review aims to evaluate the impact of paternity leave on maternal and child health by synthesizing findings from recent quantitative studies on policy implementation. Methods: Following PRISMA guidelines, a systematic search was conducted across PubMed, ScienceDirect, Scopus, EBSCOhost, and SpringerLink, targeting articles published between 2019 and 2024. Eligible studies included quantitative analyses assessing the effects of paternity leave on health outcomes among fathers, mothers, and children. Studies focusing solely on maternity leave or lacking relevant health outcomes were excluded. Two independent reviewers assessed the quality and relevance of the selected studies. Results: Of 712 articles identified, 15 met the inclusion criteria. Findings consistently showed that paternity leave was associated with reduced postpartum depression, prolonged breastfeeding duration, and improved child health outcomes, although variations in policy structure and implementation were noted. Conclusion: Paternity leave significantly contributes to maternal mental health, supports breastfeeding practices, and enhances child development. These findings underscore the necessity for more equitable and standardized paternity leave policies to support family health. Keywords: paternity leave; maternal health; child well-being; health outcomes;  family policy